Olefin-based polymer composition and film
The olefin polymer composition with controlled resin fine particles addresses blocking and scratching issues in films by enhancing resistance and slip properties, ensuring film integrity and reducing surface damage.
Patent Information
- Application Number
- JP2021009868
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-01-25
AI Technical Summary
Olefin polymer films experience blocking and surface scratching issues when stacked, with existing anti-blocking agents like inorganic substances causing surface damage and acrylic resin particles having poor affinity, leading to agent drop-off during film formation.
An olefin polymer composition containing specific resin fine particles with controlled particle size distribution and gel fraction, crosslinked with ultra-high molecular weight olefin polymers, providing improved blocking resistance and scratch resistance.
The composition achieves enhanced blocking resistance and slip properties, reducing scratches and ink peeling, while maintaining mechanical integrity and preventing surface damage during film stacking and handling.
Smart Images

Figure 0007605640000004 
Figure 0007605640000005 
Figure 0007605640000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an olefin-based polymer composition and a film. [Background technology]
[0002] Olefin polymer films are excellent in transparency and mechanical properties and are therefore widely used as various packaging materials. However, when olefin polymer films are stacked together (e.g., in a laminated or rolled form), the films adhere to each other, a phenomenon known as blocking. Thus, the blocking resistance of olefin polymer films has been improved by blending antiblocking agents (see, for example, Patent Document 1).
[0003] It is known that inorganic substances such as finely powdered silica, zeolite, talc, calcium carbonate, and diatomaceous earth are used as antiblocking agents for olefin polymer films (see, for example, Patent Document 2). However, these inorganic substances have high hardness and are amorphous, and therefore there is a problem that the film surfaces are easily damaged when films having inorganic substances disposed on their surfaces are rubbed against each other.
[0004] Also, a method of using acrylic resin particles as an antiblocking agent is known (see, for example, Patent Document 3). However, since the acrylic resin particles have insufficient affinity with olefin polymers, there is a problem that the antiblocking agent made of the acrylic resin particles falls off during film formation or secondary processing.
[0005] In order to solve the above problems, a method has been proposed in which olefin polymer particles, which have good affinity with olefin polymers, are used as an antiblocking agent. Olefin polymer particles are more flexible than the above inorganic substances, and have a higher affinity with the base olefin polymer than other polymer particles, so that they can improve the scratch resistance of the film and also improve the blocking resistance. Ultra-high molecular weight olefin polymer particles are known as such polymer particles, and the use of resin fine particles that are radiation crosslinked products of ultra-high molecular weight olefin polymers can improve the blocking resistance and the drop-off resistance of the antiblocking agent (Patent Document 4). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 6-073202 [Patent Document 2] Japanese Patent Application Publication No. 49-023245 [Patent Document 3] International Publication No. 2009 / 044925 [Patent Document 4] JP 2019-206616 A Summary of the Invention [Problem to be solved by the invention]
[0007] The olefin polymer composition disclosed in Patent Document 4 has room for improvement in terms of scratch resistance (scratch resistance) in preventing scratching of the surface of an object that comes into contact with the film or scratching of the film surface when two films rub against each other when formed into a film. The present inventors aimed to provide an olefin polymer film having even better blocking resistance and capable of suppressing scratching of the surface of an object in contact with the film or scratching of the film surface when two films are rubbed against each other. That is, the object of the present invention is to provide an olefin polymer composition which, when made into a film, has excellent blocking resistance and good slipperiness, and can suppress scratching of the surface of an object in contact with the film or scratching of the film surface when two films are rubbed against each other. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by an olefin polymer composition having the following configuration, thereby achieving the present invention.
[0009] That is, the present invention relates to the following [1] to [5]. [1] An olefin polymer composition comprising an olefin polymer (A) and resin fine particles (B) satisfying the following requirements (I) to (III): (I) The average particle size d50 is in the range of 1.0 to 35.0 μm. (II) The particle diameter d90 at which the cumulative weight fraction is 90% is in the range of 5.0 to 40.0 μm. (III) The gel fraction is in the range of 60 to 90%.
[0010] [2] The olefin polymer composition according to the above [1], wherein in the requirement (I), d50 is in the range of 3.0 to 15.0 μm, and in the requirement (II), d90 is in the range of 6.0 to 20.0 μm.
[0011] [3] The olefin polymer composition according to [1] or [2], wherein the content of the resin fine particles (B) is in the range of 0.1 to 20 parts by mass per 100 parts by mass of the total of the olefin polymer (A) and the resin fine particles (B).
[0012] [4] The olefin polymer composition according to any one of the above [1] to [3], wherein the olefin polymer (A) is at least one selected from the group consisting of ethylene polymers, propylene polymers and 4-methyl-1-pentene polymers.
[0013] [5] A film formed from the olefin polymer composition according to any one of [1] to [4] above. Effect of the Invention
[0014] According to the present invention, there can be provided a film having excellent blocking resistance and good slipperiness, and capable of suppressing scratching of the surface of an object in contact with the film or scratching of the film surface when two films rub against each other, and an olefin polymer composition capable of providing the same. In particular, suppressing scratching of the film surface makes it difficult for ink to peel off when printing is performed on the film surface, and can reduce defects of the film itself due to scratches caused during transportation, etc. [Brief description of the drawings]
[0015] [Figure 1] 1A to 1C are schematic diagrams showing how films are stacked in a blocking resistance evaluation test in the examples ((a) before stacking, (b) after stacking, (c) after sandwiching between metal plates). [Diagram 2] 1A and 1B are schematic diagrams showing how an aluminum rod is sandwiched between overlapping films in a blocking resistance evaluation test in the examples ((a) before sandwiching, (b) when sandwiching, (c) after two sheets of film are bound at the end of the test machine). [Diagram 3] FIG. 2 is a schematic diagram showing a state in which a film is fixed to a testing machine in a blocking resistance evaluation test in the examples. [Figure 4] FIG. 2 is a schematic diagram showing how overlapping films are peeled off with an aluminum rod in a blocking resistance evaluation test in the Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The olefin polymer composition according to the present invention and the film formed therefrom will now be described in detail. In this specification, unless otherwise specified, the expression "X to Y" in the explanation of a numerical range means not less than X and not more than Y. For example, "1.0 to 35.0 μm" means "not less than 1.0 μm and not more than 35.0 μm."
[0017] [Olefin Polymer Composition] The olefin polymer composition of the present invention contains an olefin polymer (A) and resin fine particles (B). The content of the resin fine particles (B) is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, further preferably 0.3 to 5.0 parts by mass, and particularly preferably 0.3 to 1.5 parts by mass, relative to 100 parts by mass of the total of the olefin polymer (A) and the resin fine particles (B). The content of the resin fine particles (B) is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, further preferably 0.3 to 5.0 parts by mass, and particularly preferably 0.3 to 1.5 parts by mass. ...20 parts by mass, more preferably 0.1 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, more preferably 0.1 to 20 parts by mass, more preferably 0.
[0018] <Resin fine particles (B)> The resin fine particles (B) satisfy the following requirements (I) to (III). Requirement (I): The average particle size d50 is in the range of 1.0 to 35.0 μm. In the present invention, the average particle diameter d50 is a value at which the integrated value of the particle shape distribution is 50% by weight, as measured by the weight-based particle size distribution method using a Coulter counter. Preferably, d50 is in the range of 3.0 to 15.0 μm. Being in the above range is preferable in terms of blocking resistance. Also, it is possible to adjust the above range by adjusting the catalyst type in the production method described below.
[0019] Requirement (II): The particle diameter d90 at which the cumulative weight fraction is 90% is in the range of 5.0 to 40.0 μm. Preferably, d90 is in the range of 6.0 to 20.0 μm. That d90 is in the above range indicates that the particle size distribution is relatively narrow, which is preferable in terms of blocking resistance and slippage. d90 can be adjusted to the above range by adjusting the catalyst type in the production method described below.
[0020] Requirement (III): The gel fraction is in the range of 60 to 90%. The gel fraction is preferably in the range of 65 to 85% by mass. When the gel fraction is in the above range, the resin fine particles (B) have appropriate hardness and cushioning properties, so that the polymer composition has good slip properties and can suppress damage to the surface of an object that comes into contact with a film obtained from the polymer composition or damage to the film surface when films are rubbed against each other. The gel fraction can be appropriately adjusted by the radiation exposure dose in the production method described below.
[0021] The gel fraction is calculated by placing 100 mg of resin fine particles (B) in 40 mL of n-decane at 145°C for 40 minutes, then dissolving the resin fine particles (B) by shaking for 1.5 hours using a thermostatic shaker under conditions of a temperature of 145°C and a shaking method of vibration method, and then hot filtering the filtrate through a PTFE (polytetrafluoroethylene) filter having a pore size of 3 μm, drying the filtrate in an evaporator, and measuring the mass (hereinafter referred to as the "insoluble mass") after vacuum drying at 100°C for 8 hours, and then calculating the gel fraction from the following formula [1]. Gel fraction (%) = (insoluble mass (mg) / 100 (mg)) × 100 [1] The melt flow rate (MFR) of the resin fine particles (B) is preferably less than 1.0 g / 10 min, more preferably 0.01 g / 10 min or more and less than 1.0 g / 10 min, and further preferably 0.01 to 0.5 g / 10 min. The MFR is measured according to JIS K7210 at 190° C. and a test load of 21.6 kg.
[0022] <Method for producing resin fine particles (B)> The resin fine particles (B) are preferably a radiation-crosslinked ultra-high molecular weight olefin polymer. Hereinafter, the radiation-crosslinked ultra-high molecular weight olefin polymer is also referred to as a crosslinked ultra-high molecular weight olefin polymer. The production method for the case where the resin fine particles (B) are a crosslinked ultra-high molecular weight olefin polymer will be described below. The ultra-high molecular weight olefin polymer used as the raw material for the crosslinked ultra-high molecular weight olefin polymer preferably satisfies the requirements (I) and (II) like the resin fine particles (B), and further preferably satisfies the following requirement (i).
[0023] Requirement (i): The intrinsic viscosity [η] measured in decalin solvent at 135° C. is in the range of 5 to 50 dl / g, preferably 5 to 40 dl / g, more preferably 5 to 30 dl / g. When the intrinsic viscosity is in the above range, it is preferable in terms of the abrasion resistance of the obtained olefin polymer composition containing the resin fine particles (B).
[0024] In the present invention, the ultra-high molecular weight olefin polymer refers to homopolymers such as polyethylene, polypropylene, poly-1-butene, and poly-4-methyl-1-pentene, and copolymers of ethylene and small amounts of other α-olefins such as propylene, 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene, but is preferably an ethylene polymer, and particularly preferably an ethylene homopolymer.
[0025] In the present invention, the ultra-high molecular weight olefin polymer can be produced, for example, by the methods disclosed in the following documents. (1) International Publication No. 2006 / 054696 (2) International Publication No. 2008 / 013144 (3) International Publication No. 2009 / 011231 (4) International Publication No. 2010 / 074073
[0026] The resin fine particles (B) made of a crosslinked ultra-high molecular weight olefin polymer can be obtained by irradiating the above-mentioned ultra-high molecular weight olefin polymer with radiation. By irradiating ultra-high molecular weight olefin polymers with radiation, molecular chains are broken and cross-linked, resulting in the molecular chains being linked together at the cross-linking points. This prevents the molecular chains from flowing freely even at temperatures above the glass transition temperature or melting point, improving high-temperature properties. Furthermore, the polymer can maintain its shape even when subjected to stress, and can retain its mechanical properties.
[0027] Radiation includes alpha rays, beta rays, gamma rays, electron beams, heavy ion beams, etc., and any of these can be used, but electron beams or gamma rays are more suitable. The radiation exposure dose varies depending on the type of monomer constituting the ultrahigh molecular weight olefin polymer used, but is usually 20 to 700 kGy, preferably 100 to 500 kGy, more preferably 200 to 500 kGy, and even more preferably 250 to 500 kGy.
[0028] When the irradiation dose is within the above range, the crosslinking reaction of the ultra-high molecular weight olefin polymer proceeds efficiently, and when the resin fine particles (B) made of the crosslinked ultra-high molecular weight olefin polymer thus obtained are used in an olefin polymer composition, re-agglomeration of the particles can be suppressed.
[0029] On the other hand, if the irradiation dose exceeds 700 kGy, the polymer may deteriorate rapidly, and if the irradiation dose is less than 20 kGy, crosslinking of the polymer chains may not proceed or may proceed slowly.
[0030] <Olefin polymer (A)> In the present invention, the olefin polymer that can be used as the olefin polymer (A) includes those obtained by polymerizing ethylene and one or more olefins selected from linear or branched α-olefins having 3 to 20 carbon atoms.
[0031] Specific examples of linear or branched α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. As these α-olefins, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, and 4-methyl-1-pentene are preferred.
[0032] In addition, in the present invention, the monomer components constituting the olefin-based polymer may include, in addition to the above-mentioned α-olefins, cyclic olefins, functionalized vinyl compounds, monomers having polar groups (e.g., carbonyl groups, hydroxyl groups, ether bond groups, etc.) and polymerizable carbon-carbon double bonds in the molecule (hereinafter also referred to as polar group-containing monomers), conjugated dienes, non-conjugated polyenes, etc., within the scope of the invention.
[0033] Examples of the cyclic olefin include cyclic olefins having 3 to 30, preferably 3 to 20, carbon atoms, such as cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4:5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene.
[0034] Examples of the functionalized vinyl compounds include aromatic vinyl compounds and alicyclic vinyl compounds. Examples of the aromatic vinyl compounds include mono- or polyalkylstyrenes such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, o-ethylstyrene, m-ethylstyrene, and p-ethylstyrene; functional group-containing styrene derivatives such as methoxystyrene, ethoxystyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylbenzyl acetate, hydroxystyrene, o-chlorostyrene, and p-chlorostyrene; and 3-phenylpropylene, 4-phenylpropylene, and α-methylstyrene. Examples of the alicyclic vinyl compounds include vinylcyclohexane and vinylcycloheptane.
[0035] Of the above-mentioned olefin polymers, preferably, an ethylene polymer, a propylene polymer or a 4-methyl-1-pentene polymer is used. Ethylene-based polymers contain ethylene as a main monomer component, and usually contain 50 mol% or more, preferably 80 mol% or more, of ethylene. Specific examples of ethylene-based polymers include high-pressure low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-low-pressure high-density polyethylene (HDPE), and very low-density polyethylene (VLDPE).
[0036] More specifically, the ethylene polymer has a density of 940 kg / m 3 More than 980kg / m 3 High density polyethylene, with a density in the range of less than 900 kg / m 3 More than 940kg / m 3 Examples of the polyethylene include low density polyethylene, medium density polyethylene, linear low density polyethylene, and very low density polyethylene, each of which has a density in the range of less than 100 nm, and a blend of these. There is no particular limitation as to which of these polyethylenes should be used, but low density polyethylene and linear low density polyethylene are preferred from the viewpoint of excellent balance between transparency and processability. The density of the ethylene polymer is measured according to the density gradient tube method of JIS K7112.
[0037] The melt flow rate (MFR) of the ethylene polymer is usually in the range of 0.01 to 100 g / 10 min, preferably 0.02 to 50 g / 10 min, and more preferably 0.02 to 30 g / 10 min. The MFR is measured according to JIS K7210 under conditions of 190° C. and a test load of 2.16 kg.
[0038] The ethylene-based polymer refers to an ethylene homopolymer, a copolymer of ethylene and a small amount of α-olefin, or a blend thereof. The copolymerization component of the copolymer is preferably 50 mol% or less, more preferably 20 mol% or less, of the total monomer units. Examples of the copolymerization component are preferably olefins having 3 to 20 carbon atoms, and examples of the olefins having 3 to 20 carbon atoms include linear or branched α-olefins, cyclic olefins, functionalized vinyl compounds, polar group-containing monomers, conjugated dienes, and non-conjugated polyenes.
[0039] The propylene-based polymer contains propylene as a main constituent monomer, and usually contains 50 mol% or more of propylene, preferably 80 mol% or more. Specific examples of the propylene-based polymer include propylene homopolymers, block copolymers or random copolymers of propylene and the above-mentioned α-olefins other than propylene, or blends thereof. There are no particular limitations on which of these should be used, but from the viewpoint of suppressing the sticky feeling of the olefin-based polymer composition, homopolymers with high melting points and rigidity are preferred.
[0040] The density of propylene polymers is usually 895 to 930 kg / m 3 The density of the polypropylene polymer is measured in accordance with the density gradient tube method of JIS K7112. The melt flow rate (MFR) of the propylene polymer is usually in the range of 0.01 to 200 g / 10 min, preferably 1 to 100 g / 10 min, more preferably 1 to 50 g / 10 min. The MFR is measured according to JIS K7210 under conditions of 230° C. and a test load of 2.16 kg.
[0041] The 4-methyl-1-pentene polymer contains 4-methyl-1-pentene as a main constituent monomer, and usually contains 50 mol% or more, preferably 80 mol% or more, of 4-methyl-1-pentene.Specific examples of the 4-methyl-1-pentene polymer include 4-methyl-1-pentene homopolymer, block copolymer or random copolymer of 4-methyl-1-pentene and at least one selected from ethylene and linear or branched α-olefins having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene), and blends thereof.
[0042] The density of 4-methyl-1-pentene polymers is usually 820 to 850 kg / m 3 The density of the 4-methyl-1-pentene polymer is measured in accordance with the density gradient tube method of JIS K7112.
[0043] The melt flow rate (MFR) of the 4-methyl-1-pentene polymer is usually in the range of 0.01 to 200 g / 10 min, preferably 1 to 100 g / 10 min, more preferably 1 to 50 g / 10 min. The MFR is measured according to JIS K7210 under conditions of 260°C and a test load of 5.0 kg. When the MFR is within the above range, the 4-methyl-1-pentene polymer has excellent moldability and mechanical strength properties.
[0044] The gel fraction of the olefin polymer (A) is preferably 0 to 5%, more preferably 0 to 1%. When the gel fraction is within the above range, fish eyes are reduced, and the olefin polymer composition is easily molded into a shape such as a film. The gel fraction of the olefin polymer (A) can be calculated by the same method as that for calculating the gel fraction of the resin fine particles (B).
[0045] <Method of producing olefin polymer composition> The olefin polymer composition of the present invention can be obtained by mixing the above-mentioned resin fine particles (B) and olefin polymer (A) components, and further, if necessary, additives described later.
[0046] The components can be mixed by various known methods, such as a multistage polymerization method, a method of mixing using a plastomill, a Henschel mixer, a V-blender, a ribbon blender, a tumbler, a blender, a kneader-ruder, etc., or a method of mixing, melt-kneading, and then granulating or pulverizing using a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc. This method makes it possible to obtain a high-quality olefin polymer composition in which the components and additives are uniformly dispersed and mixed.
[0047] <Additives> The olefin polymer composition of the present invention may further contain, as necessary, a nucleating agent, a heat stabilizer, an antioxidant, a weather stabilizer, an antistatic agent, a slip agent, an antifogging agent, a lubricant, a dye, a pigment, a natural oil, a synthetic oil, a wax, a filler, an antiblocking agent other than the crosslinked ultra-high molecular weight olefin polymer, and the like, within the scope not impairing the object of the present invention.
[0048] As the nucleating agent, dibenzylidene sorbitol-based nucleating agents, phosphate ester-based nucleating agents, rosin-based nucleating agents, benzoic acid metal salt-based nucleating agents, fluorinated polyethylene, sodium 2,2-methylenebis(4,6-di-t-butylphenyl)phosphate, pimelic acid or its salt, 2,6-naphthalene dicarboxylic acid dicyclohexylamide, etc. can be used. The amount of the nucleating agent is not particularly limited, but is preferably about 0.1 to 1 part by mass per 100 parts by mass of the olefin polymer composition. There is no particular limit to the timing of the addition, and it can be added during or after polymerization, or during molding.
[0049] As the antioxidant, known antioxidants can be used, specifically, hindered phenol compounds, sulfur-based antioxidants, lactone-based antioxidants, organic phosphite compounds, organic phosphonite compounds, or combinations of several of these can be used.
[0050] Examples of the lubricant include sodium, calcium, and magnesium salts of saturated or unsaturated fatty acids such as lauric acid, palmitic acid, oleic acid, and stearic acid, which can be used alone or in combination of two or more. The amount of such a lubricant to be added is usually 0.1 to 3 parts by mass, and preferably about 0.1 to 2 parts by mass, per 100 parts by mass of the olefin polymer composition.
[0051] As the slip agent, it is preferable to use amides of saturated or unsaturated fatty acids such as lauric acid, palmitic acid, oleic acid, stearic acid, erucic acid, and hebenic acid, or bisamides of these saturated or unsaturated fatty acids. Among these, erucic acid amide and ethylene bisstearamide are particularly preferable. It is preferable to mix these fatty acid amides in the range of 0.01 to 5 parts by mass with respect to 100 parts by mass of the olefin polymer composition.
[0052] [Film formed from olefin polymer composition] The film of the present invention can be obtained, for example, by melt extruding the above-mentioned olefin polymer composition usually in the range of 160 to 320° C. The film of the present invention may be obtained by further uniaxially or biaxially stretching a molded product obtained by molding into a film or sheet by a T-die extrusion molding method or the like. The method for molding the film of the present invention can be any method that has been conventionally used and is not particularly limited, but from the viewpoint of reducing the dynamic friction coefficient of the obtained film, a cast molding method is preferred.
[0053] In the present invention, the term "film" is a convenient name for indicating the external structure of an olefin polymer, and is a general term for a planar molded product, and this concept includes not only films but also sheets, membranes, tapes, and the like.
[0054] The film of the present invention contains the resin fine particles (B) which are the crosslinked ultra-high molecular weight olefin polymer as the material thereof as an antiblocking agent component, and therefore can improve blocking resistance and suppress scratching of the surface of an object in contact with the film or scratching of the film surface when films are rubbed against each other. The reason for this is that the resin fine particles (B) have a gel fraction in the range of 60 to 90% as required by requirement (III), and therefore the resin fine particles have appropriate hardness and cushioning properties, improving the slipperiness of the film made of the polymer composition. As a result, the protrusions originating from the resin fine particles (B) on the surface of the film are less likely to deform, and it is believed that the blocking resistance and scratch resistance of the film can be improved.
[0055] Specific examples of applications of such films include food packaging films (outer layer, inner layer, sealant, single layer), medical packaging films, pharmaceutical packaging films, industrial packaging films, stretch films, wrap films, stretched films, breathable films, moisture-proof sheets, anti-slip sheets, light-shielding films, films for laminate substrates, foamed films, building material skin materials, release films, such as release films for flexible printed circuit boards, release films for rigid boards, release films for rigid-flexible boards, release films for advanced composite materials, release films for curing carbon fiber composites, release films for curing glass fiber composites, and release films for curing aramid fiber composites. Examples of suitable applications include films, release films for curing nanocomposite materials, release films for curing filler materials, release films for semiconductor encapsulation, cushion films for release films, release films for fuel cells, release films for various rubber sheets, release films for urethane curing, release films for epoxy curing, surface protective films, such as protective films for resin plates, protective films for polarizing plates, protective films for LCD panels, protective films for optical parts, protective films for lenses, protective films for electrical parts and electrical appliances, protective films for mobile phones, protective films for PCs, protective films for mirrored plates, protective films for sheets, office supplies, sanitary supplies, and garbage bags. Examples of objects that may come into contact with the film include cardboard, paper containers, plastic films or containers, wooden containers, and metal containers, depending on the specific application of the film. EXAMPLES
[0056] The present invention will be described below with reference to examples, but the present invention is not intended to be limited thereto. [Olefin polymer (A)] In the examples and comparative examples, the following were used as the olefin polymer (A). ·LLDPE··Prime Polymer Co., Ltd. Evolue (trademark) SP2040 (density 918 kg / m 3 , MFR (190℃, 2.16kg load) 3.8g / 10min) LDPE: Mirason (trademark) 12 (density 927 kg / m 3 , MFR (190℃, 2.16kg load) 3.0g / 10min) The gel fraction of the olefin polymer (A) was determined in the same manner as the gel fraction of resin fine particles described below, and was 0% for both LLDPE and LDPE.
[0057] [Resin fine particles (B)] [Production Example 1] Production of particles (X) [Preparation of solid component (S-1)] In a 2L glass vessel equipped with a stirrer and thoroughly purged with nitrogen, 95.2g (1.0mol) of anhydrous magnesium chloride, 442mL of dehydrated decane, 260.4g (2.0mol) of 2-ethylhexyl alcohol, and 298.5g (1.0mol) of 2-octyldodecyl alcohol were charged, and the mixture was reacted at 155°C for 4 hours to obtain a homogeneous transparent solution. Next, in another 1L glass vessel equipped with a stirrer and thoroughly purged with nitrogen, the homogeneous transparent solution equivalent to 100mmol in terms of Mg atom and 610mL of dehydrated decane were charged, and 109mmol of triethylaluminum was slowly added dropwise while maintaining the liquid temperature at 0°C under strong stirring with a homogenizer (Clearmix CLM-1.5S manufactured by M Technique Co., Ltd., rotation speed 15000rpm). The liquid temperature was then raised to 80°C over 4 hours, and while maintaining the temperature at 80°C, 188 mmol of triethylaluminum was slowly added dropwise again, and the reaction was continued for another hour. After the reaction was completed, the solid portion was collected by filtration, thoroughly washed with dehydrated toluene, and 200 mL of dehydrated toluene was added to obtain a toluene slurry of the solid component (S-1). A portion of this toluene slurry was collected, and the particle size of the solid component (S-1) was measured by dynamic light scattering, which was 750 nm.
[0058] [Preparation of solid catalyst component (S'-1)] 100 mL of dehydrated toluene was placed in a 300 mL glass container equipped with a stirrer that had been thoroughly purged with nitrogen, and 5.0 mmol of the toluene slurry of the solid component (S-1) prepared above was placed in the container in terms of Mg atoms. Next, 16.7 mL of a toluene solution of a transition metal compound represented by the following formula [1] (0.001 mmol / mL in terms of Zr atoms) was dropped into the container and reacted at room temperature for 1 hour. After that, the supernatant was removed by decantation, and the container was washed three times with dehydrated toluene and twice with dehydrated decane to prepare a decane slurry of the solid catalyst component (S'-1). A portion of the obtained decane slurry of the solid catalyst component (S'-1) was sampled and the concentration was examined, and the Zr concentration was 0.000578 mmol / mL.
[0059] [ka] Ph represents a phenyl group.
[0060] [Ethylene polymerization] 500mL of dehydrated heptane was charged into a 1L autoclave equipped with a stirrer that had been thoroughly purged with nitrogen, and 100L / hr of ethylene was passed through it at room temperature for 15 minutes to saturate the liquid and gas phases with ethylene. The temperature was then raised to 70°C, and 1.00mmol of triisobutylaluminum in terms of Al atom and 0.0037mmol of solid catalyst component (S'-1) in terms of Zr atom were charged while passing ethylene at 12L / hr. The mixture was stirred for 3 minutes while maintaining the temperature, and 60mg of Emulgen E-108 (Kao Corporation) was added, immediately after which the ethylene pressure was increased. After the total pressure reached 0.3MPa·G, 3.5mL of hydrogen was added, and polymerization was carried out at 70°C for 2 hours while feeding ethylene to maintain the pressure. After polymerization was completed, the obtained polymer was washed with hexane, pre-dried at 80°C for 1 hour, and then dried at 110°C for 10 hours under reduced pressure. The yield of polyethylene was 37.0 g, the catalytic activity was 50.0 kg / mmol-Zr·h, and the intrinsic viscosity [η] measured in decalin at 135°C was 13.0 dl / g (ultra-high molecular weight ethylene polymer). The ultra-high molecular weight ethylene polymer obtained above was irradiated with an electron beam at an exposure dose of 300 kGy to obtain particles (X) made of a crosslinked ultra-high molecular weight ethylene polymer.
[0061] [Other particles] As fine particles not corresponding to the resin fine particles (B), fine particles produced under the following conditions were used. [Production Example 2] Production of particles (Y) Particles (Y) were obtained in the same manner as in Production Example 1, except that the electron beam irradiation dose was changed to 200 kGy. [Production Example 3] Production of particles (Z) Particles (Z) were obtained in the same manner as in Production Example 1, except that the electron beam irradiation dose was changed to 100 kGy. [Zeolite] EAZ-10 (a composition containing 10% by mass of synthetic zeolite and 90% by mass of low-density polyethylene as an anti-blocking agent) manufactured by Prime Polymer Co., Ltd. was used. [silica] TME172AB (a composition containing 20% by mass of spherical silica and 80% by mass of low-density polyethylene as an anti-blocking agent) manufactured by Toho Co., Ltd. was used.
[0062] [Evaluation of resin particles] The resin particles were evaluated by the following methods. The evaluation results are shown in Table 1.
[0063] <Average particle size d50, particle size at cumulative weight fraction of 90% d90> The average particle diameter d50 and the particle diameter d90 at which the cumulative weight fraction is 90% for particles (X), (Y), and (Z) were calculated from the weight-based particle size distribution by the Coulter Counter method using a Beckman Multisizer Three.
[0064] <Gel fraction> 100 mg of each of particles (X), (Y), and (Z) was left to stand in 40 mL of n-decane at 145°C for 40 minutes, and then the particles were dissolved by shaking for 1.5 hours at 145°C using a thermostatic shaker (SSC-9300 manufactured by Senshu Scientific Co., Ltd.) under the conditions of vibration method and shaking method. The resulting solution was hot filtered through a PTFE filter with a pore size of 3 μm, and the filtrate was then dried in an evaporator and vacuum dried at 100°C for 8 hours. The mass (insoluble mass) was measured, and the gel fraction defined by the following formula [1] was calculated. Gel fraction (%) = (insoluble mass (mg) / 100 (mg)) × 100 [1]
[0065] [Table 1]
[0066] [Example 1-1] 90 parts by mass of LDPE and 10 parts by mass of the resin fine particles (X) obtained in Production Example 1 were added and melt-kneaded at 190° C. using a twin-screw extruder (Technobel, KZW15-30MG) to obtain a polymer mixture.
[0067] The obtained polymer mixture and LLDPE were charged in a mass ratio of 2.5:97.5 into a cast film molding machine (D2028, manufactured by Toyo Seiki Co., Ltd.), and extrusion molding was performed at a cylinder and die temperature of 190°C and a take-up speed of 2.0 m / min to obtain a cast film having a thickness of 40 μm made of an olefin polymer composition. The obtained film was evaluated by the method described below. The evaluation results are shown in Table 2.
[0068] [Examples 1-2 and 1-3] A cast film was obtained in the same manner as in Example 1-1, except that the blending amounts of each component of the polymer mixture and the blending amount of LLDPE were changed as shown in Table 2.
[0069] [Comparative Examples 1 and 2] A cast film was obtained in the same manner as in Example 1-3, except that the resin fine particles (X) were changed to the resin fine particles (Y) or the resin fine particles (Z).
[0070] [Comparative Examples 3-1 to 3-3] A cast film was obtained in the same manner as in Example 1-1, except that the LDPE and particles (X) were changed to EAZ-10 so that the blending amounts of each component were as shown in Table 2.
[0071] [Comparative Examples 4-1 to 4-3] A cast film was obtained in the same manner as in Example 1-1, except that the LDPE and particles (X) were changed to TME172AB so that the blending amounts of each component were as shown in Table 2.
[0072] [Comparative Example 5] The LLDPE was charged into a cast film molding machine (D2028), and extrusion molded at a cylinder and die temperature of 190° C. and a take-up speed of 2.0 m / min to obtain a cast film with a thickness of 40 μm.
[0073] [Film rating] The obtained films were evaluated by the following methods. The evaluation results are shown in Table 2.
[0074] <Kinematic friction coefficient> The dynamic friction coefficient between films was measured according to JIS K7125 "Test method for friction coefficient of plastic films and sheets." The test conditions were test speed: 100 mm / min, test piece width: 63.5 mm, load: 200 g, and measurement environment temperature: 23°C.
[0075] <Evaluation of blocking resistance> Two films cut from the obtained cast film were overlapped (Fig. 1(a)(b)), and the overlapped film was sandwiched between two metal plates with a length of 20 cm and a width of 20 cm, the surfaces of which had been mirror-finished (Fig. 1(c)). The film was then left to stand for three days at 50°C with a load of 10 kg. It was then cooled to room temperature to prepare a sample for measurement. A 6 mm diameter aluminum rod was sandwiched between the two overlapping films of the measurement sample so that the distance from the aluminum rod to the bottom end of the overlapping films was 20 cm (Fig. 2(a)-(c)), and the film was fixed to an Intesco Universal Material Tester 2001 (Fig. 3). The two overlapping films were pulled upward at a speed of 20 cm / min while being peeled off using a fixed aluminum rod (Figure 4(a)-(c)), and the average load (blocking force (mN)) at which the films sheared and peeled off was measured. The average load divided by 20 cm was determined as the blocking coefficient (mN / cm) (hereafter referred to as "blocking coefficient (mN / cm)"). In Table 2, "no blocking" means that the blocking coefficient is 0, that is, the films are in contact with each other without sticking to each other.
[0076] <Tensile test> In accordance with JIS K7127-2, the tensile strength (TS: MPa) and elongation at break (EL: %) were determined using a test piece with a width of 15 mm and a pulling speed of 200 mm / min. The film was evaluated in both the TD and MD directions.
[0077] <Evaluation of scratch resistance> A Gakushin abrasion tester (manufactured by Shinto Scientific Co., Ltd.) was used to perform an abrasion test on two 20 mm x 20 mm films cut out from the films obtained in the Examples and Comparative Examples, by covering the tip of the friction element on one film and rubbing the surface of the other film with the abrasion element covered with the film. The test conditions were load: 50 g, stainless steel friction element: R45, speed: 50 mm / sec, stroke: 50 mm. The film surface was observed with a stereomicroscope when the friction element was moved back and forth 25 times, 50 times, and 100 times. The number of scratches within the range of 20 mm x 20 mm of the film was counted using STZ-171 (manufactured by Shimadzu Rika Co., Ltd.) as a stereomicroscope. In Table 2, "-" means that evaluation was not performed.
[0078] [Table 2]
[0079] [Comparison between Examples and Comparative Examples] It can be seen that Example 1-3 had fewer scratches after the Gakushin abrasion test compared to Comparative Example 1 and Comparative Example 2, which used fine particles with a gel fraction outside the range of 60 to 90%. Furthermore, since Examples 1-1 and 1-2 have a smaller content of particles (X) than Example 1-3, it is considered that if the scratch resistance was evaluated in the same manner as Example 1-3, the number of scratches would be equal to or even smaller than that of Example 1-3. Furthermore, since the Examples use olefin-based resin fine particles (B), there is less blocking or fewer scratches after the Gakushin abrasion test compared to Comparative Examples 3-1 to 4-3, which used zeolite or spherical silica. [Explanation of symbols]
[0080] 10: Universal material testing machine 14: Aluminum rod 16: Gripping means 18: Edge 20:Film 30: Frame 32: Top 34: Lifting means 36: Bottom 38: Fixing means 40:Metal Plate
Claims
1. The olefin polymer composition contains an olefin polymer (A) and resin fine particles (B) that satisfy the following requirements (I) to (III): the content of the resin fine particles (B) is in the range of 0.1 to 20 parts by mass per 100 parts by mass of the total of the olefin polymer (A) and the resin fine particles (B), The olefin polymer composition, wherein the resin fine particles (B) are polyethylene. (I) The average particle size d50 is in the range of 1.0 to 35.0 μm. (II) The particle diameter d90 at which the cumulative weight fraction is 90% is in the range of 5.0 to 40.0 μm. (III) The gel fraction is in the range of 60 to 90%.
2. The olefin polymer composition according to claim 1, wherein, in the requirement (I), d50 is in the range of 3.0 to 15.0 μm, and, in the requirement (II), d90 is in the range of 6.0 to 20.0 μm.
3. 3. The olefin polymer composition according to claim 1, wherein the olefin polymer (A) is at least one selected from the group consisting of ethylene polymers, propylene polymers and 4-methyl-1-pentene polymers.
4. A film formed from the olefin polymer composition according to any one of claims 1 to 3.
Citation Information
Patent Citations
JP1974023245A
Biaxially oriented polypropylene film
JP1994073202A
Ultrahigh-molecular-weight polyethylene molding and its production
JP1996012771A
Olefin-based polymer composition and film
JP2019206616A
A prosthetic device
WO2001045595A2
